On the pharmacokinetics of two inhaled budesonide/formoterol combinations in asthma patients using modeling approaches - Soulele, K.; Macheras, P.; Karalis, V. (PULMONARY PHARMACOLOGY & THERAPEUTICS, 2018)
Dry powder inhalers containing the budesonide/formoterol combination have currently a well-established position among other inhaled products. Even though their efficacy mainly depends on the local concentrations of the drug they deliver within the lungs, their safety profile is directly related to their total systemic exposure. The aim of the present investigation was to explore the absorption and disposition kinetics of the budesonide/formoterol combination delivered via two different dry powder inhalers in asthma patients. Plasma concentration time data were obtained from a single-dose, crossover bioequivalence study in asthma patients. Non compartmental and population compartmental approaches were applied to the available datasets. The non compartmental analysis allowed for an initial characterization of the primary pharmacokinetic (PK) parameters of the two inhaled drugs and subsequently the bioequivalence assessment of the two different dry powder inhalers. The population pharmacokinetic analysis further explored the complex absorption and disposition characteristics of the two drugs. In case of inhaled FOR, a five-compartment PK model including an enterohepatic re-circulation process was developed. For inhaled BUD, the incorporation of two parallel first-order absorption rate constants (fast and slow) for lung absorption in a two-compartment PK model emphasized the importance of pulmonary anatomical features and underlying physiological processes during model development. The role of potential covariates on the variability of the PK parameters was also investigated.
Keywords: asthma; Budesonide; Formoterol; Pharmacokinetic modeling